Combined Effect of NZVI and H2O2 on the Cyanobacterium Microcystis aeruginosa: Performance and Mechanism - Yun Kong; Lipeng Ji; Yue Wang; Jiake Li; Hao Lu; Shuhong Mo; Xianxun Wang; Liang Zhu; Xiangyang Xu; Xing Zheng (Nanomaterials, 2022)
In order to eliminate the harmful cyanobacterium Microcystis aeruginosa and the algal organic matters (AOMs) produced by M. aeruginosa, the combined process of nanoscale zero-valent iron (NZVI) and hydrogen peroxide (H2O2) has been carried out, and the removal mechanism has also been clarified. As the initial cyanobacterial cell concentration is 1.0 (±0.05) × 105 cells·mL−1, all the treatments of NZVI, H2O2, and NZVI/H2O2 have inhibition effects on both the Chl a contents and photosynthetic pigments, with the Chl a removal efficiency of 47.3%, 80.5%, and 90.7% on the 5th day, respectively; moreover, the variation of ζ potential is proportional to that of the Chl a removal efficiency. The malondialdehyde content and superoxide dismutase activity are firstly increased and ultimately decreased to mitigate the oxidative stress under all the treatments. Compared with NZVI treatment alone, the oxidation of the H2O2 and NZVI/H2O2 processes can effectively destroy the antioxidant enzyme system and then inactivate the cyanobacterial cells, which further leads to the release of photosynthetic pigments and intracellular organic matters (IOM); in addition, the IOM removal efficiency (in terms of TOC) is 61.3% and 54.1% for the H2O2 and NZVI/H2O2 processes, respectively. Although NZVI is much more effective for extracellular organic matters (EOM) removal, it is less effective for IOM removal. The results of the three-dimensional EEM fluorescence spectra analysis further confirm that both H2O2 and NZVI/H2O2 have the ability to remove fluorescent substances from EOM and IOM, due to the oxidation mechanism; while NZVI has no removal effect for the fluorescent substances from EOM, it can remove part of fluorescent substances from IOM due to the agglomeration. All the results demonstrate that the NZVI/H2O2 process is a highly effective and applicable technology for the removal of M. aeruginosa and AOMs.